1997
DOI: 10.1002/marc.1997.030180510
|View full text |Cite
|
Sign up to set email alerts
|

Polymerization of ethylene by using zirconocene catalyst anchored on silica with trisiloxane and pentamethylene spacers

Abstract: New supported catalysts on the basis of cyclopentadienylindenylzirconium dichloride (CpIndZrCl,) anchored on silica with a trisiloxane spacer (ZATS) and a pentamethylene spacer (ZAPM) were prepared and used for ethylene polymerization with modified methylaluminoxane (MAO) as cocatalyst. ZATS and ZAPM produce polyethylene with lower molecular weight but show higher activity than silica-supported CpIndZrCl, which was prepared by reacting zirconocene directly with silica, i. e., the activity of silica-supported C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(38 citation statements)
references
References 11 publications
2
36
0
Order By: Relevance
“…Recently, some researchers have reported a new immobilization method by introducing a spacer group, such as polysiloxane, between the support and metallocene. 12,13 The supported metallocene showed a better catalytic activity than previously reported, but the method introduces additional steps to the supporting process and might be less attractive from a commercial point of view.…”
Section: Introductionmentioning
confidence: 62%
“…Recently, some researchers have reported a new immobilization method by introducing a spacer group, such as polysiloxane, between the support and metallocene. 12,13 The supported metallocene showed a better catalytic activity than previously reported, but the method introduces additional steps to the supporting process and might be less attractive from a commercial point of view.…”
Section: Introductionmentioning
confidence: 62%
“…Thus, the modification of silica properties is necessary in order that it can be used more efficiently. It has been reported that the immobilization method of introducing a spacer group between the support and metallocene was found to enhance the catalytic activity [10,11]. In our previous study, the use of silanemodified silica-supported MAO with Et[Ind] 2 ZrCl 2 catalyst for ethylene/a-olefin copolymerization was investigated [12].…”
Section: Introductionmentioning
confidence: 99%
“…Control of molar mass, narrow molecular weight distributions and structural uniformity related to comonomer content are achieved through precise selection of reaction conditions. [18][19][20][21][22] In recent years, special attention has been devoted to the immobilization methodology of these catalyst systems either on organic or inorganic materials. Apart from using inorganic supports like magnesium chloride, silica, alumina, TiO 2 etc, polymeric support like pentaerythritol trimethacrylate, divinyl benzene, 2-hydroxyethyl methacrylate, styrene etc have been utilized for immobilization of metallocenes.…”
Section: Introductionmentioning
confidence: 99%